Investigating the Contributing Factors Affecting High School Students’ Self-confidence and the Solutions for Enhancement: A Case Study of Arabu Qala High School, Kandahar, Afghanistan - Rahimi, Abdullah (American International Journal of Social Science Research, 2019)
This research paper examines the contributing factors affecting high school students’ self-confidence and the solutions to enhance students’ self-confidence. The study used quantitative approach, the researcher conducted a survey study by developing a questionnaire comprising 20 items based on five Likerts scales. The data was collected from 100 high school students through random sampling which 75 were male and 25 females. The data was analysed and interpreted in terms of mean and standard deviation through SPSS software (24) version. It was concluded that different factors like, students’ feeling depressed, fear of making a mistake and others’ much focus toward students affected their self-confidence. On the other hand, factors like, teachers’ humor, students’ feeling a sense of pride and students’ encouragement and support from teachers’ side could enhance their self-confidence.